Pattern recognition technologies and applications recent advances - Verma, Brijesh; Blumenstein, Michael; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book provides cutting-edge pattern recognition techniques and applications. Written by world-renowned experts in their field, this easy to understand book is a must have for those seeking explanation in topics such as on- and offline handwriting and speech recognition, signature verification, and gender classification"--Provided by publisher.
1. Fusion of Segmentation Strategies for Off-Line Cursive Handwriting Recognition -- 2. Elastic Matching Techniques for Handwritten Character Recognition -- 3. State of the Art in Off-Line Signature Verification -- 4. An Automatic Off-Line Signature Verification and Forgery Detection System -- 5. Introduction to Speech Recognition -- 6. Seeking Patterns in the Forensic Analysis of Handwriting and Speech -- 7. Image Pattern Recognition-Based Morphological Structure and Applications -- 8. Robust Face Recognition Technique for a Real-Time Embedded Face Recognition System -- 9. Occlusion Sequence Mining for Activity Discovery from Surveillance Videos -- 10. Human Detection in Static Images -- 11. A Brain-Inspired Visual Pattern Recognition Architecture and Its Applications -- 12. Significance of Logic Synthesis in FPGA-Based Design of Image and Signal Processing Systems -- 13. A Novel Support Vector Machine with Class-Dependent Features for Biomedical Data -- 14. A Unified Approach to Support Vector Machines -- 15. Cluster Ensemble and Multi-Objective Clustering Methods -- 16. Implementing Negative Correlation Learning in Evolutionary Ensembles with Suitable Speciation Techniques -- 17. A Recurrent Probabilistic Neural Network for EMG Pattern Recognition -- Compilation of References -- About the Contributors -- Index.
Includes bibliographical references (p. 388-423) and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 13, 2010).
Keywords: Pattern perception; Pattern perception -- Data processing; Handwriting recognition; Elastic matching techniques; Signature verification; Forgery detection system; Speech recognition; Forensic analysis; Image pattern recognition; Face recognition; Occlusion sequence mining; Surveillance videos; Human detection; Static images; Visual pattern recognition; Logic synthesis; Signal processing systems; Support vector machines; Clustering methods; Electronic books